Removal of Organophosphorus Pesticide Residues in Leaf and Non-leaf Vegetables by Using Ozone Water - Surat Hongsibsong (Science Faculty of Chiang Mai University, 2019)
Organophosphorus (OPs) pesticides are the most widely used in the group of insecticides to control pests on vegetables and fruits. OPs were detected in vegetables of Thailand exceeding the maximum residue limits (MRL). Therefore, the study aims to investigate percentage removal of OPs residues at the difference of ozone levels (600 mg/h and 1,000 mg/h) and the contact times (20, 30, and 40 min) in leaf and non-leaf vegetables. Five types of leaf vegetables were Chinese cabbage, lettuce, kale, parsley and Vietnamese coriander. Five types of non-leaf vegetables were ginger, cucumber, cowpea, broccoli and onion. The results were found that the difference of ozone levels and the contact times had an effect on efficiency of OPs removal in lettuce, kale, and cowpea. the Considering average percentage of OPs removal in average contact times of 20-40 min, ozone levels at 1,000 mg/h had the highest percentage of OPs removal in an average of 65.1±12.4% for leaf vegetables and 78.4±15.6% for non-leaf vegetables. It can be concluded that the effectiveness of OPs removal in vegetables by using ozone depended on the chemical structure of OPs residues in vegetables, levels and contact times of ozone and matrix of vegetables.